2018
DOI: 10.1051/0004-6361/201731677
|View full text |Cite
|
Sign up to set email alerts
|

The Gaia-ESO Survey: Lithium enrichment histories of the Galactic thick and thin disc

Abstract: Lithium abundance in most of the warm metal-poor main sequence stars shows a constant plateau (A(Li) ∼ 2.2 dex) and then the upper envelope of the lithium vs. metallicity distribution increases as we approach solar metallicity. Meteorites, which carry information about the chemical composition of the interstellar medium at the solar system formation time, show a lithium abundance A(Li)∼ 3.26 dex. This pattern reflects the Li enrichment history of the interstellar medium during the Galaxy lifetime. After the in… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
67
1
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 44 publications
(79 citation statements)
references
References 117 publications
9
67
1
2
Order By: Relevance
“…A(Li) is predominantly higher among hotter and more massive stars. This main trend is in agreement with results of previous studies (see, e.g., Ramírez et al 2012;Luck 2017;Bensby & Lind 2018;Fu et al 2018;Pavlenko et al 2018). However, there are stars with the same atmospheric parameters and ages but different lithium abundances.…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…A(Li) is predominantly higher among hotter and more massive stars. This main trend is in agreement with results of previous studies (see, e.g., Ramírez et al 2012;Luck 2017;Bensby & Lind 2018;Fu et al 2018;Pavlenko et al 2018). However, there are stars with the same atmospheric parameters and ages but different lithium abundances.…”
Section: Resultssupporting
confidence: 93%
“…Recent high-resolution spectroscopic surveys of the Milky Way disk have reported that lithium abundances in the solar neighborhood decrease at supersolar metallicities. Delgado Mena et al (2015) were some of the first to show that the 7 Li abundance decreases with [Fe/H] > 0 and later works by Guiglion et al (2016) in the AMBRE project, Fu et al (2018) in the Gaia-ESO Survey, and Bensby & Lind (2018) from combined data of various spectrographs (e.g., FEROS and MIKE) confirmed this result. The studies by Guiglion et al (2016) and Prantzos et al (2017) tried to explain the 7 Li decreases at supersolar metallicities with stellar migration.…”
Section: Introductionmentioning
confidence: 85%
See 1 more Smart Citation
“…A bending of the Spite plateau below [Fe/H] ∼ -3 is clearly present in the data of Sbordone et al (2010). For the discs, we adopt the recent spectroscopic data from the AMBRE Project (Guiglion et al 2016) and GES (Fu et al 2018), where a distinction is made between thick and thin disc stars, basing on chemical criteria. The AMBRE catalogue consists of Li abundances for 7300 stars, homogeneously derived from high-resolution spectra in the ESO archive with an automatic method (see Guiglion et al 2016 for a description of the method and of the data validation).…”
Section: Observational Datamentioning
confidence: 99%
“…Lodders et al 2009) and young T Tauri stars (Bonsack & Greenstein 1960). To make the story a bit more complicated, a huge dispersion in Li abundances is observed for stars at disc metallicities (see Ramirez et al 2012;Delgado Mena et al 2015;Guiglion et al 2016;Fu et al 2018, among others, for recent work), while observations of extremely metal-poor stars (Sbordone et al 2010;Melendez et al 2010;Hansen et al 2014;Bonifacio et al 2015) find the Spite plateau to bend down for stars with [Fe/H]<-2.8 dex. In this work, we do not consider the first problem (the so-called cosmological Li problem).…”
Section: Introductionmentioning
confidence: 99%